The Application of the Gravity Model to the Tourism Industry of the Philippines and Select Neighboring Countries - Rahnema, Leila C (Philippine Management Review, 2023)
This study uses a modified version of the gravity model in examining the bilateral flow of tourist arrivals in the Philippines and its neighbouring ASEAN countries (Singapore, Malaysia, and Brunei). This study compares and explains the factors and pattern of tourism activities of the selected countries with their respective partner countries by looking at tourism and cultural variables that may contribute to certain tourism patterns. Among several tested variables, the results show that language (official and minority), visa policy, and availability of direct flights explain tourism flows across all selected countries. This may suggest that governments may use a wider variety of languages in their tourism campaigns and marketing collaterals. The easing of a country’s visa policy is also highly encouraged as this can stimulate international tourist arrivals. It is also important to equip the tourism industry with direct flights as this proves to be an important factor in attracting tourism arrivals.